Strategi Komunikasi Termediasi Pekerja Remote dengan Klien Multinasional - Rosalinda Manullang; Syifa Syarifah Alamiyah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to examine the mediated communication patterns employed by remote workers in their interactions with multinational clients. The background of this research is grounded in the rapid development of communication technologies and the increasing prevalence of remote work systems. The research method applied is descriptive qualitative, with data collected through in-depth interviews and documentation. The findings indicate that mediated communication is influenced by media selection, technical barriers, cultural differences, and time zone disparities. The primary strategies adopted by workers include aligning the choice of media with work requirements, clarifying instructions through written documentation, and maintaining interpersonal relationships with clients. This study contributes to the advancement of business communication scholarship, particularly in the context of cross-national remote working relationships.